Cutaneous sporotrichosis: experience at a thirdlevel hospital in Cali, Colombia = Esporotricosis cutánea: experiencia de un hospital de tercer nivel en Cali, Colombia - Castro Alegría, Luz Ángela (Iatreia, 2013)
Introduction: Sporotrichosis is a subcutaneous mycosis caused by the Sporothrix schenckii species complex; it is acquired by traumatic inoculation of the fungus. Objective: To describe the epidemiological and clinical features of a group of patients with sporotrichosis. Methodology: A retrospective and descriptive study was performed at a third-level hospital in Cali, Colombia, from January 2000 to June 2011. Records from patients having positive cultures for S. schenckii and/or periodic acid-Schiff (PAS)-diastase stain showing blastoconidia were included in the analysis. Results: The group was made up of 20 men and three women. Eight patients (34.8%) were farmers and four (17.4%) worked in construction activities. Six (26.1%) were children aged under 15 years. Sporothrix sckenckii was isolated from cultures in 22 patients (95%) and in 15 out of 21 (71.4%) blastoconidia were observed by direct examination. Fourteen patients (60.9%) had the lymphangitic form of the disease. Upper limbs were most frequently affected (16 cases; 69.6%). Twenty two patients were treated with potassium iodine. Conclusions: Lymphangitic sporotrichosis was the most common clinical form of the disease in this study. PAS-diastase stain seems to be a useful diagnostic tool for sporotrichosis